Fundamentals of geomorphology - Huggett, Richard J.; Shuttleworth, Emma (London ; New York, NY : Routledge, 2023)
"This revised and updated edition continues to provide a comprehensive introduction to the subject, exploring the world's landforms from a broad systems perspective. It covers the basics of Earth surface forms and processes, while reflecting on the latest developments in the field. Fundamentals of Geomorphology begins with a consideration of the nature of geomorphology, including its relation to society, process and form, history, and geomorphic systems, and moves on to discuss: Structure: structural landforms associated with plate tectonics and those associated with volcanoes, and folds, faults, and joints. Process and form: landforms resulting from, or influenced by, the exogenic agencies of weathering, running water, flowing ice and meltwater, ground ice and frost, the wind, and the sea; landforms developed on limestone; extraterrestrial landforms; and landscape evolution, a discussion of ancient landforms. Fundamentals of Geomorphology provides a stimulating and innovative perspective on the key topics and debates within the field of geomorphology. Written in an accessible and lively manner, it includes guides to further reading, chapter summaries, and an extensive glossary of key terms. The book is also illustrated throughout with over 200 informative diagrams and attractive photographs, all in colour. It is supported by online resources for students and instructors"--
Part I Introducing Landforms and Landscapes -- What Is Geomorphology? -- Introducing Process and Form -- Introducing History -- Geomorphology and The Earth System -- Life and Humans As Geomorphic Agents -- Part II Endogenic Processes -- Plate Tectonics And Associated Structural Landforms -- Volcanoes, Folds, And Faults -- Part III Exogenic Processes -- Weathering And Associated Landforms -- Weathering Products: Regolith And Soils -- Hillslopes -- Fluvial Landscapes -- Glacial And Glaciofluvial Landscapes -- Periglacial Landscapes -- Aeolian Landscapes -- Coastal Landscapes -- Karst Landscapes -- Planetary Landscapes -- Part IV Deep-Time Perspectives -- Long-Term Geomorphology.
"First edition published by Routledge 2002. Fourth edition published by Routledge 2017" -- Title page verso.
Includes bibliographical references and index.
Keywords: Geomorphology